NOISE EXPOSURE IN TWO TEXTILE PLANTS IN SUDAN - Alshebli A. Ahmed; Mohammed A. Awadalkarim (European Scientific Journal, ESJ, 2015)
Background: Noise is a major health threat in occupations where the level exceeds the permissible limit (85 decibel), The degree of negative effects of noise depends on its intensity, spectrum of frequency nature, duration of exposure and individual sensibility. Objectives: To assess the noise in work environment at textile factories Materials and Methods: This cross-sectional study was conducted at two textile factories in Khartoum – Sudan in 2013. The study included all workers in the two factories (n=198). Data was collected through questionnaire to obtain data about noise level perceived and variables such as work section. Noise levels (dBA) were measured by sound level meter and octave band analyzer Results: Workers in weaving sections of both factories and preparing section in Alsbagoon factory were exposed to average levels of noise above 85 dBA. Octave band analysis of the noise in Alhodhood and Alsbagoon factories in weaving, preparing and quality control sections shows high noise level in 1000Hz, 2000Hz, 4000 Hz and 6000 Hz Conclusion: Based on the findings of this study, it was demonstrated that worker are exposed to excessively high noise levels.